ANALISIS EFEKTIVITAS PENERIMAAN RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN PONOROGO - Purweni Widhianningrum; Sasongko Aji (INVENTORY: JURNAL AKUNTANSI, 2019)
This study aims to determine the effectiveness of the acceptance of motor vehicle testing levies in Ponorogo Regency in 2014-2018. Data collection techniques using primary and secondary data through interviews, observation and documentation. Data testing is done by effectiveness ratio. The results showed that the effectiveness of the acceptance of motor vehicle testing levies over the past five years was fluctuating, overall quite effective because it was less than 100%, it needed a socialization given by the government to the public that safety in driving was very important. Improving the staffing of levies collection staff to improve the process of levies collection to be optimal and increasing supervision to know whether the implementation of activities in the field in accordance with the provisions, as well as improving administrative efficiency and reduce the cost of collection.Keywords: Effectiveness, PAD, Motorized Vehicle Testing Levies.